A defined culture medium suitable for sensitive Phalaenopsis species seedlings - Choong, C. W.; Choong, S. M.; Thong, W. H. (Science Alert, 2013)
Half strength MS medium supplemented with peptone was found to inhibit growth of considerable number of Phalaenopsis species seedlings and this hamper conservation effort. It is therefore important to design a reproducible defined medium that is not selective and could support a wide range of genotypes. This could be achieved by adjusting the macronutrient concentrations. A new defined medium was designed with nitrate-nitrogen (NO3-N) to ammonium-nitrogen (NH4-N) ratio of 5 and N to S ratio of 15, buffered with 800 mg dm-3 KH2PO4 and NPK ratio of 2.0:0.8:3.1. Mean fresh weight, dry weight and root to shoot ratio was compared with control medium. In contrary to control medium that stunted growth of significant number of Phalaenopsis aphrodite, Phalaenopsis bellina and Phalaenopsis violacea seedlings, the new medium was found to significantly support growth of the seedlings and improved root development. In addition, the new medium was not selective against sensitive seedlings as the data from new medium pass normality test while data from control medium was skewed in P. bellina. This new medium is recommended for maintaining genetic diversity in conservation programs by improving seedling survival and growth in vitro.